BOOK REVIEW ON PALIMPSEST - Varvantakis, Christos; PETSINI, PENELOPE; PANAYOTOPOULOS, NIKOS (Design/Arts/Culture, 2020)
The photographs of Petsini and Panayotopoulos in “Palimpsest” trace the remnants of the Berlin Wall and of the world that it had both embraced and been embraced by: traces of the time when the Wall was a concrete, material entity, and of the trail this era has left.